PENDAPATAN USAHATANI MANGGA DIKAITKAN DENGAN KEMITRAAN DAN KARAKTERISTIK PETANI MANGGA (Kasus pada Petani Mangga di Kecamatan Sindang Kasih, Kabupaten Majalengka yang Bermitra dengan UD Wulan) - Elly Rasmikayati; Bobby Rachmat Saefudin; Yudistira Haikal Arisyi; Rani Andriani Budi Kusumo; Yayat Sukayat (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Mango farmers in Sindang Kasih Subdistrict have been in partnership with UD Wulan Jaya for quite a long time so that there should have been an impact obtained by farmers, especially related to their farming income. This study aims to analyze the relationship between the farmers' income of mango farmers who do mango partnerships with the characteristics of farmers and farmers' perceptions about aspects of the partnership. This research uses a quantitative research design by conducting a survey. The sample withdrawal technique used is a simple random sampling technique such that it is obtained 38 farmer respondents in partnership with UD Wulan Jaya. The data analysis technique used is crosstabulation analysis. The results found that the characteristics of farmers who tend to be relate to the farmer income are age, farming experience, land area and productivity per tree. Meanwhile, the aspect of partnership tends to relate to the income of mango farmers are the completeness of planning, dependence on price determination, increase in income, price guarantee, quality of production results, and mastery of technology.